2016
DOI: 10.1186/s12886-016-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

Drug discovery in ophthalmology: past success, present challenges, and future opportunities

Abstract: BackgroundDrug discovery has undergone major transformations in the last century, progressing from the recognition and refinement of natural products with therapeutic benefit, to the systematic screening of molecular libraries on whole organisms or cell lines and more recently to a more target-based approach driven by greater knowledge of the physiological and pathological pathways involved. Despite this evolution increasing challenges within the drug discovery industry are causing escalating rates of failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 91 publications
(98 reference statements)
0
33
0
Order By: Relevance
“…6), and Proper expression of surface mucins by the corneal epithelium is important not only for ocular defense against invading microbes, but also for accurate adhesion of microparticles and nanomaterials used in the modern ophthalmic drugs. 7 We have compared gene expression of surface mucins (MUC1, MUC4, and MUC16) in the 3D corneal tissue model and excised human corneal epithelium and demonstrated that all mucins were similarly expressed in both reconstructed 3D corneal tissues and excised human corneal epithelium, with MUC16 having the highest level of expression and MUC4 the lowest (Kaluzhny Y, unpublished data, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6), and Proper expression of surface mucins by the corneal epithelium is important not only for ocular defense against invading microbes, but also for accurate adhesion of microparticles and nanomaterials used in the modern ophthalmic drugs. 7 We have compared gene expression of surface mucins (MUC1, MUC4, and MUC16) in the 3D corneal tissue model and excised human corneal epithelium and demonstrated that all mucins were similarly expressed in both reconstructed 3D corneal tissues and excised human corneal epithelium, with MUC16 having the highest level of expression and MUC4 the lowest (Kaluzhny Y, unpublished data, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…7 Analysis of topical ophthalmic drug absorption is one of the main steps in the identification of compounds with favorable pharmacokinetic properties since the physical and structural barriers of the cornea, which are vitally important for eye protection, present major challenges for delivery and bioavailability. Although in vivo animal studies can be used, anatomic and physiological differences make species extrapolation unreliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Ideal candidates for improved drug delivery treatments are those ocular diseases that drastically affect patients’ quality of life including dry eye disease (DED), age-related macular degeneration (AMD), and uveitis. [24] These three common ocular diseases affect different regions of the eye and have immuno-mechanistic characteristics in their disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapies have been developed for retinal diseases [10] with some success, most notably the prostaglandin analogs for glaucoma [11] and antivascular endothelial growth factor (anti-VEGF) agents for AMD [12] and diabetic retinopathy [13]. However, there has been a chronic lack of innovation in drug discovery for retinal diseases [14], as there has been for other diseases [15]. For example, therapies targeting OS in retinal diseases have failed to show efficacy in clinical trials; examples are an antioxidant supplement mixture [16] and a hydroxylamine with antioxidant properties [17].…”
Section: Introductionmentioning
confidence: 99%